Media Theories and Approaches - Balnaves, Mark. author. aut Link
XX, 339 p.
Keywords: This unique textbook is a manageable introduction to all the theories and approaches that make up media studies, giving students an informed, balanced and global view of media today. Exploring the evolution of media internationally, this book offers theory and evidence in its discussion of past and present modes of media. Divided into four parts, readers are offered insight into critical theories and topics such as ‘Social and Global Change,’ ‘the Influence of Media,’ ‘Intercultural Communication’ and ‘News as a Form of Knowledge.’ Written by leading experts within media studies, Balnaves, Donald and Shoesmith lend their wealth of knowledge to the student reader through this text, guiding them through the progression of cultural and media studies. Genuinely global and cutting-edge, this leading textbook is the ideal learning resource for lecturers of media studies and undergraduate and postgraduate students seeking gain a thorough understanding of worldwide media, past and present. .